STRATEGI PENGEMBANGAN HERITAGE HOTEL BERBASIS BUDAYA JAWA SEBAGAI REPRESENTASI PARIWISATA BERKELANJUTAN (STUDI KASUS KUSUMA SAHID PRINCE HOTEL, SOLO) - Kusumastuti, Sendang; Suci Sandi Wachyuni; Rina Kurniawati; Asmawih (Jurnal Sains Terapan Pariwisata, 2025)
ABSTRACT: Sustainable tourism is a crucial concept in developing the tourism industry, as it not only boosts the local economy but also preserves culture and the environment. In this context, heritage hotels emerge as a form of accommodation that can blend cultural heritage with the needs of modern travelers. This study aims to explore the strategies for developing heritage hotels based on Javanese culture to represent sustainable tourism, with a case study on the Kusuma Sahid Prince Hotel in Solo. This research employs a qualitative approach with a case study method. Data was collected through interviews with relevant stakeholders, direct observations, and document analysis. The findings indicate that the Kusuma Sahid Prince Hotel has successfully integrated Javanese cultural values into its design, services, and tourism programs. The main strategies implemented include the preservation of traditional architecture, the utilization of local arts and crafts, and the development of cultural tourism programs that involve the local community. Additionally, the hotel practices sustainable tourism by implementing environmentally friendly management and community empowerment initiatives. This study concludes that the development of heritage hotels based on Javanese culture not only serves as a means of preserving cultural heritage but also as a model for sustainable tourism that provides economic and social benefits to the local community. These findings can serve as a reference for the development of other heritage hotels in Indonesia, encouraging the integration of local culture into sustainable tourism concepts. Purpose: This research aims to formulate a development strategy for Kusuma Sahid Prince Hotel (KSPH) as a heritage hotel that integrates Javanese cultural values in its operations and services so that it remains relevant in the midst of global competition. Knowing the role of KSPH in supporting sustainable tourism in Surakarta City and identifying the challenges faced by KSPH in competing with modern accommodation. Research Methods: This research uses a descriptive qualitative method with cultural theme analysis to understand the social meaning at Kusuma Sahid Prince Hotel Solo. Data were collected through interviews, intercept surveys, and literature studies. Interviews were conducted in a semi-structured manner with the help of notes, cameras, and recorders. Data consisted of primary and secondary sources, both internal and external. Implication: This research contributes theoretically to the development of literature on culture-based tourism and provides practical implications in the form of strategic guidelines for hotel managers, local governments, and other stakeholders. Keywords: strategies, heritage hotels, Javanese, sustainable tourism